Limiting tourniquet use during total knee arthroplasty improves short-term postoperative outcomes in patients with hypertension - Zhang, Lei; Ning, Yuhui; Yang, Cheng; He, Tao (Frontiers in Surgery, 2025)
IntroductionTourniquets are commonly used during total knee arthroplasty (TKA) to reduce intraoperative bleeding. However, information on the optimal tourniquet usage strategy in patients with hypertension are lacking.MethodsA retrospective analysis of 90 patients with knee osteoarthritis and hypertension who underwent primary TKA was conducted. Patients were divided into three groups: Group A (tourniquet applied before skin incision and released after wound closure), Group B (tourniquet applied before prosthesis placement and released after wound closure), and Group C (tourniquet applied before prosthesis placement and released after bone cement solidification). Outcomes measured included intraoperative and postoperative blood loss, swelling rate, visual analog scale scores, perioperative complications, and Knee Society Scores.ResultsGroup A exhibited the lowest intraoperative blood loss volume (239.26 ± 53.83 ml), but this group had significantly higher hidden blood loss, total blood loss, and transfusion volumes than Groups B and C (P < 0.05). The swelling rate and visual analog scores on postoperative day 3 were also significantly higher in Group A than in Groups B and C, as was the incidence of complications, including anemia, deep vein thrombosis, and anterior knee pain. Knee Society Scores at 4 weeks postoperatively were significantly lower in Group A than in Groups B and C.DiscussionTourniquet application before prosthesis placement and release after wound closure or bone cement solidification were associated with better short-term outcomes, reduced complications, and improved rehabilitation compared to tourniquet use during the entire procedure in patients with hypertension undergoing TKA.